Level of Participation of Students Who Participate in Extracurricular Sports Activities at SMPN 11 Banjarbaru - Saddam, Ahmad Afrizal; Anggara, Norma; Perdinanto, Perdinanto (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the level of student participation in participating in sports and extracurricular activities at SMP Negeri 11 Banjarbaru. The method used in the study is descriptive qualitative. Sampling with purposive sampling with 1 sports teacher and 7 students who are considered active in participating in sports extracurricular activities. Data collection uses more than one technique, namely observation, interviews, and documentation. The data analysis used is descriptive analysis. Based on the results of observations of the implementation of sports extracurricular activities at SMP Negeri 11 Banjarbaru, then the documentation that the researcher obtained and interviews conducted by the researcher with students who are considered active in participating in sports extracurricular activities at school, the conclusion in this study is that the level of student participation in participating in sports extracurricular activities at SMP Negeri 11 Banjarbaru is quite good, because of various intrinsic and extrinsic factors that support student participation, in addition students tend to get good support from teachers/coaches, and friends when participating in sports extracurricular activities at school, and they also get various positive experiences when participating in sports extracurricular activities.